A Report on the Use of ChatGPT in Software Engineering and Systems Analysis Courses - Albonico, Michel; Varela, Paulo Júnior (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2023: Anais do XXXVII Simpósio Brasileiro de Engenharia de Software, 2023)
ChatGPT is a natural language model that works as a virtual chat assistant. It has the potential to be used for fostering classroom discussions and addressing student needs when the professor is not accessible. Although it is still early to assess the impact of ChatGPT and similar technologies, there is a considerable discussion on social media and blogs regarding the aspirations and opportunities of utilizing ChatGPT in the software industry and education. The main perception is that ChatGPT can serve as a support tool but should not completely replace interpersonal interaction, as face-to-face dialogue remains crucial for the development of interpersonal skills and a deeper understanding of concepts. This article reports a recent classroom experience in the subjects of Software Engineering and Systems Analysis, while also analyzing ChatGPT’s responses to student inquiries.